Women’s Knowledge, Attitudes, and Experiences of Family Planning in the Geography of Inequality: A Social Capital–Informed Qualitative Study - Serap Canlı; Yeşim Çetinkaya Şen (Global Nursing Insights, 2026)
Aim: This study examined women’s knowledge, attitudes, and experiences regarding family planning (FP) within the geography of inequality through the lens of social capital.Material and Methods: This qualitative study was designed based on a phenomenological approach. The social capital framework was adopted as the theoretical basis of the study. Data were collected between September 1, 2024, and January 1, 2025, in Haymana District, Ankara Province. The participants consisted of 43 women aged 19–48 years. Data obtained through semi-structured interviews were analyzed using thematic network analysis. To ensure the validity and reliability of the findings, multiple coders were employed, peer debriefing was conducted, and the Standards for Reporting Qualitative Research guidelines were followed.Results: Family planning behavior was shaped not only by individual knowledge levels but also by the direction of social networks, institutional trust, privacy concerns, and normative pressures such as spousal approval. Women with negative fertility experiences tended to postpone or limit pregnancies and preferred long-acting contraceptive methods, while those without such experiences maintained family planning primarily through short-term methods for pregnancy prevention. A considerable number of participants reported that their sense of trust in family planning developed through communication and counseling experiences with nurses/midwives, and that this relationship helped balance normative pressures related to spousal approval.Conclusion: The interaction among network valence, institutional trust, and patriarchal norms significantly shapes family planning use in rural contexts. Strengthening privacy-sensitive service delivery, structured follow-up, and couple-centered engagement within primary care may enhance contraceptive continuity and contribute to reducing reproductive health inequalities.Implication for nursing practice: The findings highlight the role of primary care nurses and midwives in building institutional trust, safeguarding privacy, facilitating couple communication, and providing structured follow-up for side-effect management. Integrating nurse-led couple counseling and standardized follow-up protocols into primary care services may support method continuation and promote equitable access to family planning.